2011
DOI: 10.1016/b978-0-444-53815-4.00011-x
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal, longitudinal assessment of intracortical microstimulation

Abstract: The fundamental obstacle to neuroprostheses based on penetrating microstimulation is the tissue's response to the device insertion and to the application of the electrical stimulation. Our long-term goal is to develop multichannel microstimulation of central nervous tissue for clinical therapy. The overall objective of this research is to identify the optimal parameters for a chronically implanted microstimulation device. In particular, the work presented here focuses on the effects of repeated stimulation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 47 publications
7
48
1
Order By: Relevance
“…Statistical analysis showed that site size was a statistically significant factor ( p  < 0.01), while post-implant time was not. While microstimulation studies have revealed a pattern of a sharp increase in impedance within the first 2–3 weeks post-implantation followed by a decay to some baseline (18, 21, 31, 32), the findings here follow impedance patterns shown in long-term implantation studies applying microelectrode arrays solely for neural recording (17, 20). …”
Section: Discussionsupporting
confidence: 72%
“…Statistical analysis showed that site size was a statistically significant factor ( p  < 0.01), while post-implant time was not. While microstimulation studies have revealed a pattern of a sharp increase in impedance within the first 2–3 weeks post-implantation followed by a decay to some baseline (18, 21, 31, 32), the findings here follow impedance patterns shown in long-term implantation studies applying microelectrode arrays solely for neural recording (17, 20). …”
Section: Discussionsupporting
confidence: 72%
“…A recent study from our lab investigating the depth-dependency of microstimulation-induced behavioral responses found that, over time, the most superficial electrode sites along a linear microelectrode array required the greatest increase in stimulation current to effectively drive a behavioral response (Koivuniemi et al ., 2011). Detailed histological analysis of tissue around intact devices used for depth-depended behavioral studies may clarify this link.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding effects of the instrumentation, which are unlikely given that five different stimulators were used in this study, there are (at least) four mechanisms that would lead to a decrease in impedance: (1) an electrical 'loosening' of the glial and/or other tissue encapsulation (cf [27,28,30,34,38]); (2) the formation of iridium oxide or other electrochemical effects at the metal interface (cf [27,38]); (3) failure of the insulation of the electrode (cf [42]); (4) failure of the electrode substrate or other aspect of the device (i.e., wire bonds or connector) (cf [35]).…”
Section: Mechanisms Underlying the Effect Of Chronic Icms On The Elecmentioning
confidence: 99%